MORAL LESSONS FROM THE BIBLICAL ACCOUNT OF JOSEPH (GEN. 37 -42) AND THEIR USEFULNESS IN THE DAILY LIFE OF STUDENTS OF ALVAN IKOKU FEDERAL UNIVERSITY OF EDUCATION, OWERRI - Alaribe, Gilbert N; Nzeh, Atracta A (Top Educational Review Journal (TERJ), 2025)
The study examined the moral lessons from the biblical account of Joseph and the daily life of the students of Alvan Ikoku Federal University Education, Owerri. Two research questions and two hypotheses guided the study. Descriptive survey research design was adopted for the study. Sample size of 300 students was drawn from a population of regular Christian students using purposive-accidental sampling techniques. A researcher developed rating scale titled: Biblical Joseph’s Life Story Moral Lessons Rating Scale (BJLSMLRS) was used for data collection. It was validated by 5 experts. It has two clusters: A and B with internal consistency reliability coefficients of 0.86 and 0.88 respectively. Mean and standard deviation were used to answer the research questions, while the z-test statistics was used to test the hypothesis at 0.05 levels of significance. Results showed that while the extent of students’ awareness of the moral lessons from the biblical account of Joseph is significantly above the expected average, the extent to which they are determined to uphold them in their daily life is significantly below the expected average level. Owing to the findings and their implications, the following recommendations were made: the family needs to put more effort in strengthening these moral lessons/values in the life of the children; the teachers/lecturers who teach and relate with the students should be the epitome of Joseph’s account so that the students can easily emulate them; the religious organizations both within and outside the school should put more effort in emphasizing these moral lessons/values so that they can be instilled in students; and the school should ensure that these moral lessons/values like honesty, integrity, responsibility, respect, fleeing from all forms of sexual immorality and wickedness are considered in developing policies and encouraging workers, especially those who are Christians, to show them in their dealings with students